1990
DOI: 10.1002/lsm.1900100511
|View full text |Cite
|
Sign up to set email alerts
|

Laser in situ keratomileusis

Abstract: A new laser refractive procedure is being developed in a rabbit model. With a modified microkeratome, central corneal flaps were created. An ArF excimer laser was used to produce 3-mm-diameter circular ablations on the central part of the exposed stromal bed. One group of animals was sacrificed immediately postoperatively, and both the dissected and ablated areas were studied using scanning electron microscopy. A second group of animals was sacrificed 4 weeks postoperatively. In this group, the subsequent heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
135
0
20

Year Published

1991
1991
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 496 publications
(161 citation statements)
references
References 10 publications
1
135
0
20
Order By: Relevance
“…Refractive surgery: Laser in situ keratomileusis (LA-SIK) [67] involves the removal of tissue in the bulk of the cornea (stroma) to correct for nearsightedness, farsightedness, or astigmatism. Suction immobilizes the eyeball, and a microkeratome blade partially separates the epithelium, leaving a hinge of uncut tissue at one end.…”
Section: Eye Surgerymentioning
confidence: 99%
“…Refractive surgery: Laser in situ keratomileusis (LA-SIK) [67] involves the removal of tissue in the bulk of the cornea (stroma) to correct for nearsightedness, farsightedness, or astigmatism. Suction immobilizes the eyeball, and a microkeratome blade partially separates the epithelium, leaving a hinge of uncut tissue at one end.…”
Section: Eye Surgerymentioning
confidence: 99%
“…Studies conducted in rabbits, which have a similar inervacional structure to the human cornea, have demonstrated the reappearance of peripheral neurites around the sixth week following PRK (17) . Likewise, Pallikaris et al observed recovery of central corneal sensitivity to values considered normal or near normal in the third month after PRK (18) . In the mitomycin C group of the present study, no recovery of cor neal esthesia to normal values was observed ay 90 days after the procedure, with a mean value of 39.2 (P<0.001).…”
Section: Discussionmentioning
confidence: 89%
“…While widely used in clinical practice, complications from laser in situ keratomileusis (LASIK) have been reported since its description by Pallikaris 1 in 1990. Here, we report a case of a young man with an unusual fundus appearance after LASIK-related corneal penetration and lens dislocation.…”
Section: Sir Interesting Fundus Lesion After Lasik Mishapmentioning
confidence: 99%